Performance of potato cultivars grown in the organic production system - Passos,Sara (2022)
ABSTRACT In this study we evaluated the performance of potato cultivars in the organic production system, aiming to identify those more productive and less damaged by Phytophthora infestans and Diabrotica speciosa. The experiment was conducted during the 2013/2014 and 2014/2015 crop seasons. Cultivars Ágata, Aracy Ruiva, Vitória, Clara, Eliza, Catucha and Cris were assessed for severity and area under disease progress curve (AUDPC) of P. infestans, external holes and internal galleries caused by D. speciosa, and tuber yield. Most cultivars reacted positively to P. infestans and D. speciosa. ‘Ágata’ was the most susceptible cultivar, with P. infestans severity close to 100% and AUDPC significantly higher than the other cultivars. D. speciosa larvae external damages were more intense in ‘Eliza’ than in ‘Clara’ and ‘Catucha’. ‘Eliza’ was also among the most internally damaged cultivars in both years, while ‘Catucha’ and ‘Vitória’ were among the least internally damaged. The results indicate ‘Catucha’ and ‘Clara’ as the most suitable for organic cultivation among the studied materials.